PENGEMBANGAN BAHAN AJAR DIGITAL MENGGUNAKAN FLIP BUILDER PADA MATERI NEGARAKU INDONESIA - Yulistiani, Sella; Kurnia, Dadang; Safitri, Nurlinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of learning resources available in schools becomes less attractive still using printed teaching materials that only contain writing, so that students' interest in learning becomes less. The purpose of this study is to develop digital teaching materials using the flip builder application on the material Negaraku Indonesia grade IV SDN Ciawi 03 Bogor Regency. This type of research is Research and Development (R&D) development research with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Digital teaching materials using flip builder have been developed and tested through the validation of media experts with 94% of the reviews categorized as